Slovak Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
As in other European transition economies, unemployment statistics in Slovakia are provided by two different sources: an official register of the unemployed (maintained by the National Labor office) and a Labor Force Survey (undertaken by the Statistical Office). The register of the unemployed, established in 1990, provides monthly statistics on the number of workers who are included in the register, whereas the Labor Force Survey, undertaken since 1993, provides quarterly data on employment and unemployment derived by interviewing a sample of 10,250 households.